(untitled) (Annals of Medical Research, 2021)
Characterized by progressive cerebellar ataxia, cutaneous and conjuctival telangiectasia, ocular apraxy, immunodeficiency, and increased risk of malignancy, ataxia-telangiectasia is a rare neurodegenerative disorder that shows signs of autosomal recessive transmission. The ataxia-telangiectasia gene is located in chromosome 11q22-23. Various degrees of abnormalities in T and B cell immunities have also been described. It is known that the incidence of both T cell and B cell leukemia and lymphoma increased compared with the general growth of the population in Turkey. T cell malignancy can be seen at any age though B cell malignancy is more common at older ages. This report presents the case of two siblings who were diagnosed with ataxia-telangiectasia. The two siblings formerly had another sibling who was diagnosed with ataxia-telangiectasia and died from leukemia. Taking these two cases as the staring point, this study focuses on the clinical manifestations, affected systems and treatment of ataxia-telangiectasia.